Stereoselective Synthesis of Z Fluoroalkenes through Copper‐Catalyzed Hydrodefluorination of gem‐Difluoroalkenes with Water. Issue 43 (22nd September 2017) - Hu, Jiefeng; Han, Xiaowei; Yuan, Yu; Shi, Zhuangzhi
Abstract: A copper catalytic system was established for the stereoselective hydrodefluorination of gem‐difluoroalkenes through C−F activation to synthesize various Z  fluoroalkenes. H2 O is used as the hydrogen source for the fluorine acceptor moiety. This mild catalytic system shows good‐functional group compatibility, accepting a range of carbonyls as precursors to the gem‐difluoroalkenes, including aliphatic, aromatic, and α, β‐unsaturated aldehydes and even ketones. It serves as a powerful synthetic method for the late‐stage modification of complex compounds. Abstract : From A(ll) to Z : A copper catalytic system was established for the stereoselective hydrodefluorination of carbonyl‐derived gem ‐difluoroalkenes with water through C−F activation. This route employs readily available aldehydes or ketones, cheap fluorine and hydrogen sources, and an earth‐abundant metal as the catalyst, and it can be employed to construct Z  fluoroalkenes without considering the Z / E configuration of the substrates or intermediates.